Section 3.3-problems-1

# Section 3.3-problems-1 - f ′ ( x ) = 2 x ( x 2-1) 2 6. f...

This preview shows pages 1–2. Sign up to view the full content.

to (aqt73) – Section 3.3 – isaacson – (55826) 1 This print-out should have 7 questions. Multiple-choice questions may continue on the next column or page – fnd all choices beFore answering. 001 10.0 points ±ind the value oF f ( a ) when f ( t ) = 2 t + 3 t + 2 . 1. f ( a ) = 1 ( a + 2) 2 2. f ( a ) = - 1 ( a + 2) 2 3. f ( a ) = - 2 ( a + 2) 2 4. f ( a ) = 1 a + 2 5. f ( a ) = 2 ( a + 2) 2 6. f ( a ) = - 2 a + 2 002 10.0 points Determine the derivative oF f when f ( x ) = p 1 2 P 2 / 3 . 1. f ( x ) = p 1 2 P x 1 / 3 2. f ( x ) = 0 3. f ( x ) = 2 3 p 1 2 P 1 / 3 4. f ( x ) does not exist 5. f ( x ) = 1 3 x 1 / 3 003 10.0 points ±ind the x -coordinate oF all points on the graph oF f ( x ) = x 3 - 2 x 2 - 4 x + 2 at which the tangent line is horizontal. 1. x -coord = 2 3 2. x -coords = - 2 3 , 2 3. x -coord = 2 4. x -coord = - 2 3 5. x -coord = - 2 6. x -coords = 2 3 , - 2 004 10.0 points ±ind the derivative oF f when f ( x ) = x ( x + 7) . 1. f ( x ) = 2 x - 7 x x 2. f ( x ) = 3 x - 7 2 x 3. f ( x ) = 2 x + 7 x x 4. f ( x ) = 3 x - 7 x x 5. f ( x ) = 2 x + 7 2 x 6. f ( x ) = 3 x + 7 2 x 005 10.0 points ±ind the derivative oF f when f ( x ) = x x - 1 x .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
to (aqt73) – Section 3.3 – isaacson – (55826) 2 1. f ( x ) = 1 1 + 1 x 2 2. f ( x ) = 2 x x 2 - 1 3. f ( x ) = - 2 x ( x 2 - 1) 2 4. f ( x ) = - 2 x x - 1 5.
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: f ′ ( x ) = 2 x ( x 2-1) 2 6. f ′ ( x ) =-1 1-1 x 2 006 10.0 points Find the value of F ′ (2) when F ( x ) = f ( x ) f ( x )-g ( x ) and f (2) = 3 , f ′ (2) = 4 , g (2) = 2 , g ′ (2) = 5 . 1. F ′ (2) = 7 2. F ′ (2) = 22 3. F ′ (2) = 23 4. F ′ (2) =-23 5. F ′ (2) =-7 007 10.0 points Determine g ′ ( x ) when g ( x ) = 5 + xf ( x ) √ x , and f is a di±erentiable function. 1. g ′ ( x ) = 2 xf ( x ) + x 2 f ′ ( x )-5 √ x 2. g ′ ( x ) = 2 xf ( x ) + x 2 f ′ ( x )-5 x √ x 3. g ′ ( x ) = xf ( x )-x 2 f ′ ( x ) + 5 x √ x 4. g ′ ( x ) = xf ( x ) + 2 x 2 f ′ ( x ) + 5 √ x 5. g ′ ( x ) = xf ( x ) + 2 x 2 f ′ ( x )-5 2 x √ x 6. g ′ ( x ) = xf ( x )-2 x 2 f ′ ( x ) + 5 2 x √ x...
View Full Document

## This note was uploaded on 06/14/2011 for the course MATH 305G taught by Professor Cathy during the Spring '11 term at University of Texas.

### Page1 / 2

Section 3.3-problems-1 - f ′ ( x ) = 2 x ( x 2-1) 2 6. f...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online